2014
DOI: 10.2967/jnumed.114.144386
|View full text |Cite
|
Sign up to set email alerts
|

High Prognostic Value of 18F-FDG PET for Metastatic Gastroenteropancreatic Neuroendocrine Tumors: A Long-Term Evaluation

Abstract: This study aimed to evaluate the long-term prognostic usefulness of 18 F-FDG PET for patients with metastatic gastroenteropancreatic neuroendocrine tumors (GEPNETs). Methods: Thirty-eight patients with metastatic GEPNETs were prospectively enrolled. Initial check-up comprised CT scan, 111 In-pentetreotide scintigraphy (SRS), and 18 F-FDG PET. Only 18 F-FDG PET-positive lesions with a maximum standardized uptake value (SUV max ) greater than 4.5 or an SUV ratio (SUV max tumor to SUV max nontumoral liver tissue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 13 publications
10
126
2
3
Order By: Relevance
“…In their study, SUV max for 68 Ga-DOTANOC correlated with prognosis, whereas that for 18 F-FDG did not. Several reports have indicated that 18 F-FDG positivity is associated with a worse prognosis, although to our knowledge most of these studies did not specifically investigate the role of SUV max (22,38). In our study, we found that metastases demonstrated by either tracer correlated with a shorter survival, with bone metastases correlating with the worst prognosis.…”
Section: Discussionsupporting
confidence: 55%
“…In their study, SUV max for 68 Ga-DOTANOC correlated with prognosis, whereas that for 18 F-FDG did not. Several reports have indicated that 18 F-FDG positivity is associated with a worse prognosis, although to our knowledge most of these studies did not specifically investigate the role of SUV max (22,38). In our study, we found that metastases demonstrated by either tracer correlated with a shorter survival, with bone metastases correlating with the worst prognosis.…”
Section: Discussionsupporting
confidence: 55%
“…Vice versa, 68 Ga-SSA PET/CT in cases presenting higher Ki-67 values (.50%), even if positive, will likely not affect management. The added value of 18 F-FDG in welldifferentiated NENs (G1 and G2) is still under debate, and no international consensus has been reached (49)(50)(51)(52)(53).…”
Section: Clinical Valuementioning
confidence: 99%
“…This point underlines the better prognostic value of 18 F-FDG than of SRS, with a survival rate of 0% at 4 y in cases of 18 F-FDG positivity, regardless of the SRS results, and 70% for patients with positive SRS results and negative 18 F-FDG results (1).…”
Section: Replymentioning
confidence: 86%
“…We have read with great interest the comments of Hofman et al regarding our recently published study (1) about the high prognostic value of 18 F-FDG PET for metastatic neuroendocrine tumors (NETs). In that prospective study, patients with 18 F-FDG-avid NETs, defined by a standardized uptake value (SUV) exceeding 4.5 or a tumor-to-nontumor SUV ratio (T/NT ratio) exceeding 2.5, had dramatically decreased overall survival (OS) in comparison with patients with 18 F-FDG-negative NETs.…”
Section: Replymentioning
confidence: 92%
See 1 more Smart Citation